TVET teaching implementation: competency, challenges and motivation - Anwar, Khairunnisa; Mohamad, Mimi Mohaffyza (2022)
The purpose of this research is to determine the competencies, obstacles, and motivations associated with the implementation of TVET instructions at Vocational Colleges. The competency aspects analyzed are the knowledge and skills. The problems that educators have in implementing TVET teaching, as well as the motivation of educators in implementing TVET teaching, are also examined. This study involved 76 TVET educators from selected Vocational Colleges. The data was collected using a survey form and analyzed using a descriptive method to get the mean score and standard deviation. The findings of the study revealed that the level of knowledge, skills, and motivation of the educators is high while the challenges assessed got a moderate level of score. In summary, the implementation of teaching among TVET teachers has an element of high teaching competence but in facing the challenges while implementing teaching has a variety of responses. Apart from knowledge, skills, motivation, and challenges, strengthening from the aspect of teaching delivery is a necessity towards the consolidation of quality teaching in TVET.